EVALUASI KEGIATAN BELAJAR DAN MENGAJAR BAHASA INGGRIS MARITIM MENGGUNAKAN NEED ANALYSIS APPROACH - Endah Fauziningrum; Ever Nicolas (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2019)
The cadets need to master Maritime English skills to communicate between ship and shore, between crew members, between crew and captain, between crew and passangers. So, the cadets’ efficiency in English is highly expected. Therefore, the purpose of this research are to find out the the needs of maritime cadets in English for Specific Purposes class and problem/s faced by Nautical cadets in Maritime English class. Population sampling for this research is Nautical cadets of STIMART "AMNI" Semarang on English for Specific Purpose in Maritime English class. This research uses need analysis approach to interpret the data and using qualitative approach to describe the data. The results of this research are the language abilities that the maritime cadets mostly needed is speaking with 75%. And current problems that faced by cadets toward Maritime English course is cadets find difficulties to master in pronunciation and speaking skill because of their anxiety to make a mistake also lack of time allocation in Maritime English course. Need analysis is important thing in teaching learning process, especially in English for Specific Purposes. By conducting need analysis, the lecturer can get some information about the cadets’ need which plays an important role in designing the materials that will be given to the cadets.Keywords : Need Analysis Approach, teaching and learning, English for Specific Purposes, Maritime EnglishTaruna sangat perlu untuk menguasai keterampilan Bahasa Inggris maritime untuk berkomunikasi antara kapal dan kapal, kapal dan stasiun pantai, antara kru dan kapten antar kru serta antara kru dan penumpang. Oleh karena itu, tujuan dari penelitian ini adalah untuk mengetahui kebutuhan taruna akademi maritim akan English for Specific Purposes di kelas  Bahasa Inggris Maritim. Sampel yang digunakan dalam penelitian ini adalah taruna Program Studi D3 Nautika STIMART "AMNI" Semarang di kelas English for Specific Purpose Bahasa Inggris Maritim. Penelitian ini menggunakan Need Analysis Approach untuk menginterpretasikan data dan menggunakan pendekatan kualitatif untuk menjelaskan data. Hasil dari penelitian ini adalah kemampuan bahasa yang paling dibutuhkan oleh taruna akademi maritim yaitu berbicara dengan 75%. Dan masalah yang dihadapi taruna dalam kegiatan belajar dan mengajar di kelas Bahasa Inggris Maritim yaitu menemukan kesulitan untuk menguasai keterampilan pengucapan dan berbicara karena kecemasan untuk membuat kesalahan juga kurangnya alokasi waktu dalam mata kuliah Bahasa Inggris Maritim. Analisis kebutuhan adalah hal yang penting dalam proses belajar mengajar, terutama dalam English for Specific Purposes. Dengan melakukan analisis kebutuhan, dosen dapat memperoleh informasi tentang kebutuhan taruna sehingga merancang materi yang akan diberikan kepada taruna.Kata kunci : Need Analysis Approach, Pengajaran, Pembelajaran, English for Specific Purposes